Analisis Pengaruh Keragaman Produk Terhadap Keputusan Pembelian Konsumen Toserba Borma Kota Bandung, Indonesia - Al Bukhori, Gina Nurlatipah Perawati (International Journal Administration, Business & Organization, 2022)
This study aims to determine the effect of product diversity on consumer purchasing decisions in the city of Bandung, Indonesia. Respondents came from consumers who bought their various needs at the modern market closest to their place of residence, namely the Toserba Borma, Bandung City. This study uses quantitative descriptive methods, validity and reliability tests, normality tests, and data analysis using simple linear regression. The sample in this study was 113 respondents. Data was collected by distributing questionnaires to respondents who met the criteria. The results showed that the diversity of products in Borma, Bandung City is very significant on the buying interest of Borma consumers. This means product diversity can improve purchasing decisions.